Kritik Pemikiran Arab: Metode Dekonstruksi Mohammed Arkoun - Soekarba, Siti Rohmah (UI Scholars Hub, 2006)
Mohammed Arkoun is one of an international Islamic modern thinker that his thought comes into Islamic thinking discourses in Indonesia recently. His Islamic thought were influenced by the modern philosophy concepts such as